MINAT SISWA DALAM PEMBELAJARAN PJOK DI SD AGRECIA - Manalu, Yogi Prananda Parmahotan; Vai, Aref; Rahmatullah, M. Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to determine the level of interest ofAgracea Elementary School students in physical education subjects. Research wasconducted on students at Agresia Elementary School. The study will be carried out inJuly-December 2024. The subjects of this research are all 27 grade 5 students atAgresia Elementary School, so the total population for this study is 27 people. Based onthe research results, the level of student interest in learning physical education at SDAgresia is divided into 3 indicators, namely the level of interest of students at SDEgresia is at a very good level with a level of progress. was 80.74%, while the level offulfillment of the role of physical education teachers was considered good at 78.63%and the provision of facilities and infrastructure was considered good at 65.61%.Overall, the level of interest of SD Agresia Pekanbaru students in physical educationsubjects is 76.30%, which means that the level of interest of SD Agresia students inphysical education subjects is at a good level.Keywords: Interest, Physical Education